A Study on User Satisfaction with the Use of E-Books in Academic Libraries - Rosmaryati Ab Rahman; Hasnah Hashim; Endang Fitriyah Mannan (Anuva: Jurnal Kajian Budaya, Perpustakaan, dan Informasi, 2025)
This paper examines user satisfaction towards the utilization of e-books in academic libraries but more concentrated to Universiti Teknologi MARA (UiTM) Kota Bharu Campus. This study will analyze the satisfying elements of usability, accessibility and content quality of the application on user satisfaction, with the theoretical framework based on Technology Acceptance Model (TAM), Information Systems Success Model (ISSM) and Expectation Confirmation Theory (ECT). As a quantitative study design, a structured online questionnaire with 317 valid cases was used, descriptive statistics, Pearson correlation, and multiple regressions were conducted in SPSS. The results indicate that the three independent variables were positively related to user satisfaction and usability had a stronger association than the other independent variables. The significant dependence between the moderating factors and predicted variable is the ability to explain 75.6 percent of the variance of the satisfaction amongst the users. Even though the issue of accessibility is relatively less important, its contribution is essential in making e-book platforms accessible readily. This finding shows that academic libraries should improve e-book platform usability, content quality, and system accessibility in order to achieve better user satisfaction. The practical implications of the given findings are rather useful in the promotion of digital libraries and the body of knowledge regarding user-centred within an academic setting.